Counseling in Inflammatory Bowel Diseases: A Question, an Observation, and a Proposal - Pellicano, Rinaldo (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Pellicano R. Counseling in inflammatory bowel diseases: A question, an observation, and a proposal. Turk J Gastroenterol. 2022;33(2):168.